2022
DOI: 10.1111/dom.14643
|View full text |Cite
|
Sign up to set email alerts
|

Humoral immune response to COVID‐19 vaccination in diabetes is age‐dependent but independent of type of diabetes and glycaemic control: The prospective COVAC‐DM cohort study

Abstract: Aims: To investigate the seroconversion following first and second COVID-19 vaccination in people with type 1 and type 2 diabetes in relation to glycaemic control prior to vaccination and to analyse the response in comparison to individuals without diabetes.Materials and methods: This prospective, multicentre cohort study analysed people with type 1 and type 2 diabetes and a glycated haemoglobin level ≤58 mmol/mol (7.5%) or >58 mmol/mol (7.5%), respectively, and healthy controls. Roche's Elecsys anti-SARS-CoV-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
69
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(82 citation statements)
references
References 29 publications
11
69
2
Order By: Relevance
“…That study showed that substantial quantities of neutralizing antibodies were elicited post-vaccination, about five times the seropositivity threshold. However, in contrast to our findings and to the findings by Sourij et al, both SARS-CoV-2 IgG and neutralizing antibodies titers were lower in people with T2DM than people without DM [ 7 , 8 ].…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…That study showed that substantial quantities of neutralizing antibodies were elicited post-vaccination, about five times the seropositivity threshold. However, in contrast to our findings and to the findings by Sourij et al, both SARS-CoV-2 IgG and neutralizing antibodies titers were lower in people with T2DM than people without DM [ 7 , 8 ].…”
Section: Discussioncontrasting
confidence: 99%
“…In this study, we showed that the humoral immune response to the BNT162b2 mRNA vaccine was similar between people with DM and people without DM in three different measurements (T1, T2, T3). In a previous study, a total of 86 healthy controls and 161 people with DM were enrolled, and antibody levels were measured 7 to 14 days after the first vaccination, as well as 14 to 21 days after the second vaccination (86% received the BioNTech/Pfizer, 8.7% the Moderna and 5.3% the AstraZeneca vaccine) [ 8 ]. In the unadjusted analysis the study showed highest antibody levels after second vaccination in people with type 1 DM ( p = 0.022 vs. healthy controls and p = 0.013 vs. people with type 2 DM).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations